Cultural norms create a preference for traditional birth attendants and hinder health facility-based childbirth in Indonesia and Ethiopia: a qualitative inter-country study. Issue 3 (3rd May 2020) - Nasir, Sudirman; Zerihun Kea, Aschenaki; Steege, Rosalind; Limato, Ralalicia; Tumbelaka, Patricia; Datiko, Daniel Gemechu; Syafruddin,; Kok, Maryse; Ahmed, Rukhsana; Taegtmeyer, Miriam
ABSTRACT: Cultural barriers to health facility-based childbirth are a common experience worldwide despite wide variations in context. Close-to-community (CTC) maternal health providers play an important role in bridging communities and health systems and their role in maternal health are particularly key. This study explored the views of CTC maternal health providers and other community members on the cultural barriers to health facility-based childbirth in two districts in Indonesia and six districts of Sidama Zone, southern Ethiopia. Employing a qualitative approach, we conducted 110 semi-structured interviews (SSIs) and 7 focus group discussions (FGDs) in Indonesia; 44 SSIs and 14 FGDs in Ethiopia. Participants in both contexts included mothers, husbands, male community members, traditional birth attendants (TBAs), village heads, local administrators, district health officials, maternal health-care workers and CTC maternal health providers. Despite significant geographical and cultural differences, the main findings were similar in the two countries' study areas. These included: strong cultural-religious beliefs; culture of shyness and privacy around pregnancy; highly gendered decision-making related to pregnancy and childbirth; and preference for the TBA care. TBAs' close proximity at the time of childbirth and their adherence to traditional practices were important factors influencing preference for TBAs. These cultural barriers interplay with geographical, transportation and financial factors hindering pregnant women from giving birth at a health facility. Intensifying health promotion on health facility-based childbirth, increasing collaboration among CTC maternal health workers e.g. midwives, health extension workers and TBAs, and enhancing responsiveness to traditional practices may overcome cultural barriers to institutional childbirth in Indonesia and Ethiopia.